2020
DOI: 10.1002/ejhf.1818
|View full text |Cite
|
Sign up to set email alerts
|

Trends in prevalence of comorbidities in heart failure clinical trials

Abstract: AimsThe primary objective of this systematic review was to estimate the prevalence and temporal changes in chronic comorbid conditions reported in heart failure (HF) clinical trials.Methods and resultsWe searched MEDLINE for HF trials enrolling more than 400 patients published between 2001 and 2016.Trials were divided into HF with reduced ejection fraction (HFrEF), HF with preserved ejection fraction (HFpEF), or trials enrolling regardless of ejection fraction. The prevalence of baseline chronic comorbid condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
87
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(93 citation statements)
references
References 37 publications
1
87
1
4
Order By: Relevance
“…The reported prevalence of comorbidities varied with HF severity (5). As shown in Figure 1, we summarized the prevalence of major comorbidities according to the different organs and systems involved, such as hypertension (65%), atrial fibrillation (45%), chronic obstructive pulmonary disease (COPD)/asthma(40%), iron deficiency (30%), diabetes (40%), chronic kidney diseases (CKD) (25%), obesity (45%) (6,7), ischaemic heart disease (50%), hyperlipidaemia (55%) (8), depression (40%) (9)(10)(11), sleep apnea (40%) (12), sarcopenia (40%) (13) and liver dysfunction (10%) (14). The high prevalence of multi morbidity is associated with poor prognosis and heavy heath burdens, and therapy for multi morbidity in HF is still a challenge (15).…”
Section: Introductionmentioning
confidence: 99%
“…The reported prevalence of comorbidities varied with HF severity (5). As shown in Figure 1, we summarized the prevalence of major comorbidities according to the different organs and systems involved, such as hypertension (65%), atrial fibrillation (45%), chronic obstructive pulmonary disease (COPD)/asthma(40%), iron deficiency (30%), diabetes (40%), chronic kidney diseases (CKD) (25%), obesity (45%) (6,7), ischaemic heart disease (50%), hyperlipidaemia (55%) (8), depression (40%) (9)(10)(11), sleep apnea (40%) (12), sarcopenia (40%) (13) and liver dysfunction (10%) (14). The high prevalence of multi morbidity is associated with poor prognosis and heavy heath burdens, and therapy for multi morbidity in HF is still a challenge (15).…”
Section: Introductionmentioning
confidence: 99%
“…However, patients included in randomized clinical trials (RCTs) usually differ from those that physicians manage every day in clinical practice; they are usually younger, more stable, have fewer comorbidities, higher adherence rates to therapy, and attend more follow-up visits than real-world patients 17,18 . In a recent systematic review of 118 trials published between 2001 and 2016, Khan et al found that 72% excluded patients with ≥ 1 comorbid condition among dementia, anaemia, diabetes mellitus, severe or uncontrolled hypertension, chronic kidney www.nature.com/scientificreports/ disease (CKD), atrial fibrillation, chronic liver disease, stroke, cancer, and COPD 19 . CKD was the most common exclusion criterion (47% of trials).…”
Section: Discussionmentioning
confidence: 99%
“…The inclusion and exclusion criteria in our study have been very strict; therefore the resulting analyzed population is aligned with the current definitions of HFpEF [ 1 , 26 , 27 ]. In support of our selection criteria, a recent review concerning heart failure clinical trials concludes that only 27% of the HFpEF trials report patient-specific comorbidities, and unfortunately, most studies exclude a number of patients because of their comorbidities [ 28 ]. However, patients with DM, anemia, CKD, pulmonary disease were not excluded from our study, thus allowing a more realistic overview of this heterogeneous population.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important since Khan et al underline the need to also include a multi-morbid population in the HFpEF trials to create a broader image, closer to real-life cases. These combined pathologies bear the potential to induce acute presentations and heart failure decompensation [ 28 ]. In agreement with their publication we have observed in our study a moderate, although statistically significant, correlation between the number of comorbidities and HFR.…”
Section: Discussionmentioning
confidence: 99%